Dipstik leukosit esterase untuk diagnosis servisitis mukopurulenta Kajian pada wanita pekerja seks - Meita Dewayani Meita Dewayani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Mucopurulent cervicitis (MPC) is an endocervical inflammation that causes a variety of complications, including infertility. The diagnosis of MPC is usually confirmed by counting the number of leucocytes using a Gram stain of an endocervical swab. This method requires trained personnel, microscopic equipment and time to read the result, so the detection of MPC in primary health care setting is often difficult. The leucocyte esterase dipstick (LED) is an easy and rapid method designed for detecting leucocytes, although its role for diagnosing MPC needs to be clarified. In order to test whether LED could be used as Gram stain substitute for diagnosing MPC, a diagnostic study was conducted among 145 female sex workers seeking reproductive health care from Griya Lentera STD clinic, managed by the Indonesia Planned Parenthood Association in Yogyakarta. Endocervical swabs were taken from each subject for Gram staining, a gonorhoeae culture and LED examination. The result showed that compared to Gram staining, the LED had 96.7% sensitivity, 64.81% specificity, a Positive Predictive Value (PPV) of 82.2% and a Negative Predictive Value (NPV) of 92.1 %. Compared to the gonorrhoeae culture, the LED had 100% sensitivity, 32.2% specificity, a PPV of 25.23% and a NPV of 100%. This study concluded that among women at high risk for STD infection the LED could be used as a Gram stain replacement in the diagnose of MPC and as an initial screening method to eliminate MPC caused by gonorrhoeae.Key words : mucopurulent cervicitis - gram stain - leukocyte esterase dipstick - gonococcal microculture -female sex workers.